An elastic-viscoplastic creep model for describing creep behavior of layered rock - Li, Yukun; Shen, Mingxuan; Du, Bin; Yuan, Shisong (Frontiers in Materials, 2023)
To describe the full-stage creep behavior of layered rock accurately, a new elastic-viscoplastic creep model is proposed based on fractional order theory in this manuscript, which consists of a Hooke elastomer, a fractional Abel dashpot, a Kelvin body, and a new nonlinear visco-plastic component. The nonlinear creep model can not only describe the changes in three creep stages (primary creep, steady-state creep and accelerating creep) but also reflect the influence of different bedding angles of rock. The constitutive equations of the nonlinear creep model are deduced by the empirical model method and plastic theory method, respectively. The parameters of the nonlinear creep model are identified using the Levenberg-Marquardt algorithm from Origin. It shows that the creep model in this paper are highly consistent with the experimental data under different load levels, creep stages and bedding angles, and the accuracy and rationality of the model are verified. Moreover, the creep constitutive equations for layered rock derived by the two methods have the same fitting effect on the same set of experimental data.